Usability Evaluation And Satisfaction Of Mobile Game Players Using SUS, GEQ, And PENS - Hikmah, Lailatul; Kurniawan, Dedy; Sanjaya, M Rudi; Rifai, Ahmad (Jurnal Ekonomi, 2024)
The rapid development of digital technology has a significant impact on the entertainment industry, especially on mobile games. Evaluation is needed to ensure usability, experience, and player satisfaction. The rapid increase in the mobile game industry makes evaluating these aspects important to ensure that games are not only attractive from the virtual, but also provide an optimal playing experience. The SUS method is used to measure the usability of the game, while GEQ evaluates the dimensions of the playing experience, such as emotion and involvement, and PENS measures the psychological needs of players, such as competence, autonomy, and connectedness. This study evaluates the Mobile Legends game using the System Usability Scale (SUS), Game Experience Questionnaire (GEQ), and Player Experience of Need Satisfaction (PENS). The results of 101 data obtained showed a SUS score of 52.89 which is included in the "ok" category at Low Marginal which requires improvement. GEQ and PENS show a positive playing experience even though some psychological needs have not been fully met. The combination of these three methods provides a comprehensive understanding of the user experience that can be a reference for the development of future mobile games.